2017
DOI: 10.3389/fped.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

A Challenging Case of Hepatoblastoma Concomitant with Autosomal Recessive Polycystic Kidney Disease and Caroli Syndrome—Review of the Literature

Abstract: We report a rare case of an 18-month-old female with autosomal recessive polycystic kidney disease, Caroli syndrome, and pure fetal type hepatoblastoma. The liver tumor was surgically resected with no chemotherapy given. Now 9 years post resection she demonstrates no local or distant recurrence and stable renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
5
0
4
Order By: Relevance
“…Prognostic significance of several HB pathology variants. In the past, several HB variants have been postulated to be associated with inferior survival of patients (that is, microtrabecular or anaplastic variant) 18 , 19 . On the contrary, pure fetal well-differentiated HB (PF-HB) was associated with very good survival which was proven in subsequent COG studies.…”
Section: Controversiesmentioning
confidence: 99%
“…Prognostic significance of several HB pathology variants. In the past, several HB variants have been postulated to be associated with inferior survival of patients (that is, microtrabecular or anaplastic variant) 18 , 19 . On the contrary, pure fetal well-differentiated HB (PF-HB) was associated with very good survival which was proven in subsequent COG studies.…”
Section: Controversiesmentioning
confidence: 99%
“…Quite often, CS is associated with autosomal recessive polycystic kidney disease (ARPKD) [3]. Left untreated, pathology in CS is progressive and can lead to clinical complications including frequent episodes of bacterial cholangitis, formation of bile stones, portal hypertension, hepatobiliary degeneration, and cholangiocarcinoma [4,5,6,7]. Hepatic transplantation is indicated once severe cholangitis, malignant transformation, or even suspicion of malignancy is present.…”
Section: Introductionmentioning
confidence: 99%
“…It can manifest with hepatic fibrosis alone, or it can be an important component of various fibrocystic diseases involving multiple systems ( Supplementary Table S2) [38][39][40][41][42][43]. Also, CHF is observed in X-linked and autosomal dominant inherited disease like oral-facial-digital syndrome type 1 and autosomal dominant polycystic kidney disease (ADPKD), respectively, and is reported in Prader-Willi syndrome, abernethy malformation, and different types of hepatic 5 Gastroenterology Research and Practice nodules (e.g., hepatocellular adenoma and hepatoblastoma) in individual case reports [44][45][46][47]. In our cases, we found that CHF could coexist with CBA and ABCB4 mutation, but their association with CHF has not been verified.…”
Section: Discussionmentioning
confidence: 99%